Constellation of Cognitive Impairment, Spasticity, and Lower Motor Neuron Disease Secondary to Possible Whipple Disease - Aliş, Ceren; Gündüz, Ayşegül; Kızıltan, Güneş; Apaydın, Hülya (Cerrahpaşa Medical Journal, 2021)
Herein, we report a patient with dementia, parkinsonism, and motor neuron disease owing to possible central nervous system involvement of Whipple disease. Although co-existence of dementia, parkinsonism, and second-order motor neuron involvement may be seen in some degenerative disease complexes, excluding a reversible condition is a necessity. The critical issue in diagnosing our patient was the presence of gastroparesis and arthritis in history associated with progressive supranuclear palsy-like clinical features. Impairment in any domain of cognition may be observed in Whipple disease. Our patient had prominent attention and memory deficits. To our knowledge, this is the first case of generalized lower motor neuron involvement with cognitive deficits and parkinsonism in Whipple disease. Cite this article as: Aliş C, Gündüz A, Kızıltan G, Apaydın H. Constellation of Cognitive Impairment, Spasticity, and Lower Motor Neuron Disease Secondary to Possible Whipple Disease. Cerrahpaşa Med J 2021; 45(1): 49-52.